Psychosocial experiences of children aged 6-12 years old, who are affected by HIV & AIDS: An application of Action Learning Model. - KOLA , JESCA K.; Bonny , ASSANI WAKENGE (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
Children aged 6-12years, who are affected by HIV/AIDS struggle with traumatizing psychosocial experiences stemming from loss of their parent(s) then moving in with already burdened caregivers. Lack of basic needs, neglect, abuse and minimal communication form adults resulted in children making bad unguided decisions. Unable to express their feelings, silence left them fearful and untrusting. They missed school often, were sick on and off and poorly took their ARVs. Lack of national interventional policies targeting 6-12year olds created a gap and impacted them negatively. Action learning theory was applied to the children to promote their resilience. Methods: Both qualitative and quantitative designs were applied using a phenomenological approach throughout the research to collect data. Sixteen children were purposively sampled following the results of children’s health as determined by the Child Status Index tool. Over a period of three months, action learning strategies were applied to them during the weekly meetings and follow-ups at home. Key Informant interviews were conducted with policy holders, administration officers, opinion leaders and caregivers. Focused discussions were held with community health leaders. Inductive qualitative approach was used on content analysis of data and Statistical Package for the Social Sciences was used to analyze quantitative data. Results: No previous action learning Model studies on this age group were found. Weekly interactions eased the impact and helped children to unreservedly share their traumatizing experiences. School attendance improved, frequent sicknesses lessened and ART intake was improved. Conclusions: Applying action learning Model on children experiencing traumatic psychosocial difficulties improves their coping mechanisms and promotes their resilience.